CATCH FISHERMAN EMPOWERMENT STRATEGY IN IMPROVING TOURISM DEVELOPMENT IN KARANGANTU NUSANTARA FISHERY PORT (PPN) CITY OF SERANG , BANTEN - Awan Dharmawan; Dimas Handrianto (Jurnal Kebijakan Pembangunan Daerah, 2021)
ABSTRACT The economic crush experienced by capture fishermen at PPN Karangantu, Serang City, Banten has forced the fishermen to move by making good use of the facilities and infrastructure and developing the potential for tourism development. This is done for the sake of survival and improvement of the level of the economy. Given these conditions, a research was conducted with the aim of reviewing the empowerment strategies carried out by catch fishermen in increasing income through tourism development at PPN Karangantu. The research was carried out with a descriptive qualitative approach and to examine and answer the existing problems, a SWOT analysis was prepared. The results showed that the strategy of empowering fishermen to increase their income through tourism development at PPN Karangantu requires active participation and support from the parties. PPN Karangantu, Serang City Government, Community Leaders and State Apparatus, so that PPN Karangantu can become a more attractive tourist destination accompanied by improvement and better management of facilities and facilities. Key words : Empowerment, Fisherman Capture, Strategy Tourism Development